A Study of the Efficacy of Skin Needling and Platelet Rich Plasma in the Treatment of Acne Scars - Shivani Ranjan; RS Gupta; S Gupta (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Permanent scars are the major complications of acne. Correction of scars is the priority for acne patients. Platelet-rich plasma (PRP) may be useful in the treatment of atrophic acne scars by promoting collagen deposition. Skin needling also releases growth factors, initiate a cascade of wound healing resulting in collagen production. Hence, skin needling and PRP should act synergistically to improve acne scars.